Paratenon-Sparing Quad Tendon Graft Harvest - Ran Atzmon MD; Anna Bartsch MD; Kinsley Pierre BS; Monica S. Vel BS; Nick N. Trivedi MD; Seth L. Sherman MD (SAGE Publishing, 2024)
Background: In recent years, the quadriceps tendon has gained popularity for primary anterior cruciate ligament (ACL) reconstruction surgery due to its robustness, easy access, and ability to be tailor-made to each patient. However, concerns remain regarding potential complications associated with quadriceps tendon harvest, including impaired healing and damage to the extensor mechanism. Indications: Preserving the quadriceps paratenon, which is a source of blood supply, nutrients, and therapeutic cells during ACL reconstruction surgery, may improve postoperative outcomes by mitigating potential adverse effects associated with quadriceps harvest. As a result, it may also facilitate the quadriceps healing process and postoperative rehabilitation. Technique Description: The incision area is marked approximately 1 cm below to 3 cm above the proximal patellar pole, and the skin is dissected from the underlying tendon, exposing both the quadriceps and its paratenon. Once the tendon insertion to the patella's proximal pole is visualized, a double-blade knife is used to make a full-thickness 2-cm longitudinal cut, taking care not to cut over 2 cm of the overlying paratenon. Then, the distal end of the tendon is safely detached from the patella followed by placing continuous whip sutures, which are then loaded on a graft harvesting system and cannula. The cannula is gently plunged underneath the paratenon while applying tension on the whip sutures with the knee flexed to 90°. Then, the cannula is twisted repeatedly under the paratenon until the desired length of 61/2 to 7 cm is reached. Again, care is taken not to lever the tendon and to harvest it along its anatomic course. Finally, the quad tendon cutter is used to transect the quad at its proximal end. During the procedure, knee extension and flexion are used to aid visualization and access to the tendon's ends. Results: Preservation of the quadriceps paratenon during its harvest for ACL reconstruction surgery can potentially improve postoperative outcomes by facilitating healing and reducing friction between the tendon and neighboring tissue. Discussion/Conclusions: Preserving the quadriceps paratenon during ACL reconstruction surgery is a technique that can be easily performed and has the potential to improve postoperative outcomes. By preserving the paratenon, surgeons can reduce potential adverse effects associated with quadriceps harvest, such as impaired healing and damage to the extensor mechanism. Based on our experience and the available literature, we believe that preserving the paratenon during quadriceps tendon harvest is a valuable technique that surgeons should consider when performing ACL reconstruction surgery. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.